Nutritional Status of the Members of the Factory Worker-Headed Households of Four Villages of Gazipur District - Dipti, SS; Tuazon, MAG; Kabir, KA (Journal of Agriculture & Rural Development, 2008)
The study was undertaken to determine the nutritional status of factory worker-headed households in four semi-urban villages (i.e. Board Bazar, Signboard, Bhogra and Zogitola under Gazipur district) during June 2005. Data were collected from 100 randomly selected factory workers who are head of the households in the study area covering a total of 457 people and their 86 pre-school children. Prevalence rates of malnutrition were determined by using weight-for-age, height-for-age and weight-for-height classification. A total of 73.3% pre-school children were underweight, 72.1% had stunted growth and 27.9% were wasted. Prevalence of underweight for age was also found in 71.5% of school children. Body mass index (BMI) was used to assess either under-nutrition (chronic energy malnutrition) or over-nutrition in adults (20 years and over). Prevalence of chronic energy malnutrition among adult members was found 57.7% for male and 56.5% for female. DOI: http://dx.doi.org/10.3329/jard.v6i1.1666 J Agric Rural Dev 6(1&2), 119-124, June 2008